2013
DOI: 10.1371/journal.pone.0068591
|View full text |Cite
|
Sign up to set email alerts
|

The Plastid Genome of Najas flexilis: Adaptation to Submersed Environments Is Accompanied by the Complete Loss of the NDH Complex in an Aquatic Angiosperm

Abstract: The re-colonization of aquatic habitats by angiosperms has presented a difficult challenge to plants whose long evolutionary history primarily reflects adaptations to terrestrial conditions. Many aquatics must complete vital stages of their life cycle on the water surface by means of floating or emergent leaves and flowers. Only a few species, mainly within the order Alismatales, are able to complete all aspects of their life cycle including pollination, entirely underwater. Water-pollinated Alismatales includ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
92
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 85 publications
(99 citation statements)
references
References 45 publications
7
92
0
Order By: Relevance
“…Nevertheless, the circular chloroplast genomes of most seed plant species are highly conserved in terms of gene arrangement. In general, they consist of a large single copy (LSC) and a small single copy (SSC) regions, which are separated from each other by two long identical but in an opposite direction sequences known as the inverted repeats (IR) (Peredo et al, 2013;Wang et al, 2013). The size of chloroplast genome ranges from 120 to 220 kb, where variation in size is caused usually by the enlargement or reduction of the IR influencing LSC or SSC nearby.…”
Section: Resultsmentioning
confidence: 99%
“…Nevertheless, the circular chloroplast genomes of most seed plant species are highly conserved in terms of gene arrangement. In general, they consist of a large single copy (LSC) and a small single copy (SSC) regions, which are separated from each other by two long identical but in an opposite direction sequences known as the inverted repeats (IR) (Peredo et al, 2013;Wang et al, 2013). The size of chloroplast genome ranges from 120 to 220 kb, where variation in size is caused usually by the enlargement or reduction of the IR influencing LSC or SSC nearby.…”
Section: Resultsmentioning
confidence: 99%
“…() and Peredo et al. () hypothesized that loss of plastid NADH dehydrogenase function is tenable in submerged habitats, if there is reduced photooxidative stresses in subtidal zones. However, the far slower rates of carbon dioxide diffusion in water versus air may actually increase the likelihood of photooxidative stress in submerged aquatics, by starving them of carbon dioxide, unless such plants are also well‐shaded.…”
Section: Discussionmentioning
confidence: 99%
“…Les et al, 1997), functional loss of the enzyme complex must not be a prerequisite for survival in a submersed marine environment. A third loss was hypothesized by Iles et al (2013) to have occurred in the common ancestor of Najas, Thalassia and Vallisneria in Hydrocharitaceae (see also Peredo et al, 2013; who confirmed the loss in Najas). Our expanded taxon and gene sampling clarifies the taxonomic extent of the loss in Hydrocharitaceae (Fig.…”
Section: Repeated Functional Loss Of the Plastid Nadh Dehydrogenase Cmentioning
confidence: 94%
See 1 more Smart Citation
“…Iris is a diverse genus with bearded and non-bearded species; species with rhizomes, bulbs, or tuberous roots; mesic and xeric species; and species with unifacial or dorsiventral leaves that may be large and obvious or reduced and only a few centimeters tall. Researchers have found divergent plastid genomes that may be related to habitat or plant life form (Delannoy et al 2011;Logacheva et al 2011;Wang and Messing 2011;Peredo et al 2013). The diversity of habitats utilized and morphological forms present in Iris provides an opportunity to explore plastid genome diversity between sister clades and among more distantly related clades across diverse plant forms and modes of habitat utilization.…”
Section: Discussionmentioning
confidence: 99%